Czechoslovak film industry on the way from private business to public good (1918-1945). Issue 4 (19th May 2022) - Doležalová, Antonie; Moravcová, Hana
ABSTRACT: Based on archival materials examined for the first time, this study reveals the process of monopolisation of the film industry in interwar Czechoslovakia. The study analyses (1) the narrative surrounding the state involvement in the film business and (2) the structure and effects of the government subsidies to the film production. The study shows (1) that the narrative emphasized the national-educational and national-consciousness role of film and (2) that the practice which the system of state support established made it possible to finance the production of Czechoslovak films. At the same time, the increasing level of state intervention during the Protectorate led to the rapid completion of the monopolisation of the industry.